INNOVATION AND CONTRIBUTION TO FORMULATE SPECIFIC RESEARCH QUESTIONS OR HYPOTHESES BASED ON MATERIALS DEVELOPMENT (Conferencea, 2024)
This article highlights the importance of formulating clear research questions or hypotheses when developing materials, and provides several examples and approaches to assist in this process.